2018
DOI: 10.1021/acsami.8b02709
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Insensitive Aggregates of Pt(II) Complexes as Phosphorescent Labels of Proteins with Luminescence Lifetime-Based Readouts

Abstract: The synthesis and photophysical properties of a tailored Pt(II) complex are presented. The phosphorescence of its monomeric species in homogeneous solutions is quenched by interaction with the solvent and therefore absent even upon deoxygenation. However, aggregation-induced shielding from the environment and suppression of rotovibrational degrees of freedom trigger a phosphorescence turn-on that is not suppressed by molecular oxygen, despite possessing an excited-state lifetime ranging in the microsecond scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…This is in agreement with previous observations reported in the bibliographic literature, where different Pt(II) and Pd(II) complexes showed emission as monomers, dimers or aggregates. [19][20][21]32,35,50 Φ L(air) ± 2 (%)…”
Section: Photophysical Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in agreement with previous observations reported in the bibliographic literature, where different Pt(II) and Pd(II) complexes showed emission as monomers, dimers or aggregates. [19][20][21]32,35,50 Φ L(air) ± 2 (%)…”
Section: Photophysical Characterizationmentioning
confidence: 99%
“…Notably, Pt(II) complexes can form aggregates both in solution and in the solid state. [18][19][20][21][22] Such interactions involve the d 8 -configured metal center and facilitate the intermolecular coupling between d z 2 orbitals protruding out of the coordination plane. Hence, aggregation leads to a red-shifted emission originating from an excimer or an metal-metal-to-ligand charge-transfer ( 3 MMLCT, d-d-) state, which is insensitive to quenching by 3 O 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these clusters can even act as donors in energy transfer processes, the free monomeric species in solution are nonemissive. 13 Moreover, we have shown that self-assembled micelles based on tailored copolymers doped with Pt(II) complexes can be tracked by optical and electron microscopy, due to their oxygen-insensitive luminescence and contrast enabled by the high atomic number. The resulting dual readout was employed to track their uptake and localization in eukaryotic cells with high spatiotemporal resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Strassert, Viappiani and co-workers have exploited self-assembled Pt II complexes as labels for other biomolecules, such as bovine serum albumin (BSA, Figure 18). 143…”
mentioning
confidence: 99%